P120: Microarray research of allelic imbalance in breast cancers during neoadjuvant chemotherapy. Issue 1 (November 2015) - Tsyganov, M.; Ibragimova, M.; Litviakov, N.; Cherdyntseva, N.
Abstract : Background: For single nucleotide polymorphism – SNP (SNP – Single Nucleotide Polymorphism) is characterized by phenomenon of allelic imbalance (AI). The phenomenon of allelic imbalanced (AI) is typical of many genes in different malignancies. Allelic imbalanced may result allelic deletions (loss of one copy of the locus) or amplification of one allele, resulting in only a single allelic variant of SNP is determined in the tumor in the PCR. Phenomenon of AI in tumors of breast cancer (BC) is considered in one or more genes. The phenomenon of AI during chemotherapy (CT) and especially in the longer format of the gene had not previously been studied. Thus, the aim of this work was to study microarray imbalanced allele in mammary tumors during neoadjuvant chemotherapy (NCT). Materials and methods: The study included 26 breast cancer patients with stage IIA – IIIC. The patients in the neoadjuvant mode received 2–4 courses of chemotherapy regimens FAC or CAX. DNA from 26 paired samples before treatment and operational samples were isolated by dialing QIAampDNA miniKit (Qiagen, Germany). Microarray analysis was performed on DNA chips of high density company Affymetrix (USA) CytoScanTM HD Array, which contains more than 750 thousand SNP. Microarray analysis was performed on SNP genotypes DNA tumor tissue before and after treatment for each patient and recorded as change occurring allelic imbalanced tumor tissue genotype (AA > AB > AB AA BB > AB > AB BB) during therapy. Results: The frequency of the AI in breast tumor during NCT was highly variable (within 0.9–66.5%) of the studied SNP (6850 – 497, 979 SNP). For each patient, frequency shift genotype (homozygous in heterozygous genotype, and vice versa) was calculated as a percentage of all the shifts. Changes in the wild or mutant heterozygous genotypes (AA or BB > AB) were combined into one group; the second group was the sum of the change in the heterozygous genotype homozygous wild genotype or the mutant (AB > AA or BB). We have found that the direction of the AI was significantly associated effect of NCT. In the group of patients with partial regression, the direction of AI change from homozygous to heterozygous genotype often occurs (AA or BB > AB) (9/14, 64%), whereas patients with no response to the NCT (with stabilization or progression) have the opposite effect. All these patients (12/12 cases) have the direction of the change of AI from heterozygous genotype to homozygous (AA or AB > BB) ( p = 0.00071). AI during chemotherapy at the level of the marked tendency (Log-rank test, p = 0.062) is associated with 5-year metastasis-free survival. Low metastasis-free survival rate is observed in patients with AI in the direction of the change from the heterozygous to homozygous genotype, while 100% survival is noted in patients with change from homozygous to heterozygous genotypes, and this imbalanced t allele is a favorable prognostic factor. Conclusion: Allelic imbalanced in breast tumor during NCT phenomenon is massive and may affect up to 67% of SNP. AI may occur in the direction of change from homozygous to heterozygous genotype, and it is associated with a good response to treatment and 100% metastasis-free survival. Apparently, this can be explained by the fact that the change from homozygous genotypes to heterozygous occur due to partial destruction of tumor cells by chemotherapy, resulting in the increase of stromal elements. In contrast, AI in the direction change from heterozygous to homozygous genotype during NCT is associated with no response to chemotherapy due to metastasis and occurring of new mutant clones in the tumor.